25. Effect of Maintenance Temperature and Shelf Life of Tilapia (Oreochromis niloticus) Fillet Stored in Temperature -20 C on Total Count Bacteria - Nurdiani Muliana Sitakar; Nurliana N; Faisal Jamin; Mahdi Abrar; Zakiah Heryawati Manaf; Sugito S (Jurnal Medika Veterinaria, 2016)
This study aims to determine the effect of storage time on the total number of bacteria in nile tilapia (Oreochromis niloticus) flesh stored at a temperature of 20 C and at different retention time. This study used split plot completely randomized design (CRD) with 2 treatment maintenance temperature of 29 C and 35 C. Experimental animals used were 30 nile tilapia fish grouped into five storage group namely 0 (P0), 7 (P1), 14 (P2), 21 (P3), and 28 (P4) days. The results showed that total number of bacteria found in fish flesh was higher than normal standard based on ISO 7388:2009 which was 5x105 cfu/g. The average of total numbers of bacteria in flesh of nile tilapia fish reared in 29 C on P0, PI, PII, PIII, and PIV were 6.55±0.19, 6.99±0.07, 6.96±0.08, 6.96±0.28, and 7.18±0.15, respectively. While the average of total numbers of bacteria in flesh of nile tilapia fish maintained in temperature of 35 C were 6.68 ± 0.10, 7.00±0.05, 7.19±0.12, 7.24±0.12, and 7.35±0.09, respectively. Total number of bacteria in nile tilapia flesh was affect significantly (P0.05) by temperature and storage temperature maintenance. In conclusion, storage time and different tempera ure maintenance of nile tilapia can increase total amount of bacteria on fish flesh.